The Rise of Digital Money - Adrian, Tobias (FinTech Notes; FinTech Notes, 2019)
This paper marks the launch of a new IMF series, Fintech Notes. Building on years of IMF staff work, it will explore pressing topics in the digital economy and be issued periodically. The series will carry work by IMF staff and will seek to provide insight into the intersection of technology and the global economy. The Rise of Digital Money analyses how technology companies are stepping up competition to large banks and credit card companies. Digital forms of money are increasingly in the wallets of consumers as well as in the minds of policymakers. Cash and bank deposits are battling with so-called e-money, electronically stored monetary value denominated in, and pegged to, a currency like the euro or the dollar. This paper identifies the benefits and risks and highlights regulatory issues that are likely to emerge with a broader adoption of stablecoins. The paper also highlights the risks associated with e-money: potential creation of new monopolies; threats to weaker currencies; concerns about consumer protection and financial stability; and the risk of fostering illegal activities, among others.